Systematic Literature Review: Efektifitas Problem-Based Learning Berbantuan Media Pembelajaran terhadap Literasi Matematis Siswa Indonesia - Praja, Novian Aditya; Susilo, Bambang Eko (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2025)
This study aims to systematically analyze the trends, focus, and effectiveness of the implementation of Problem-Based Learning (PBL) assisted by learning media on improving students' mathematical literacy in Indonesia. The approach used is a Systematic Literature Review (SLR) with reference to the guidelines of Kitchenham and Charters. Data were collected from 26 scientific articles published between 2021 and 2025 obtained through the Google Scholar database. Article inclusion criteria in this study were set to ensure the relevance and quality of the sources, namely they must be journal publications indexed by Sinta or Google Scholar, specifically discussing students' mathematical literacy in the implementation of Problem-Based Learning assisted by learning media, and written in Indonesian or English. Analysis was conducted on aspects of the objectives, types and designs of the research, types of media used, learning materials, educational levels, and the effectiveness of the implementation of media-assisted PBL. The results of the review indicate that most studies focused on improving mathematical literacy using a quantitative approach through a quasi-experimental design and the ADDIE model. Digital learning media, particularly GeoGebra, is the most widely used and has proven effective in fostering understanding of abstract concepts. Furthermore, studies show that high school and vocational high school (SMA/SMK) students and geometry are the most frequently researched topics. Overall, the integration of PBL with learning media has been shown to effectively improve mathematical literacy, critical thinking skills, and student engagement, making it an innovative strategy for strengthening the quality of mathematics learning in Indonesia